Best Practice in Gender - Roseberry, Wendy (World Bank, Washington, DC, 2012)
The study assessed women's constraints, priorities and needs with respect to agricultural extension. Extension activities and messages should be based on diagnosis which includes gender differences in activities, resources, opportunities and benefits. Women have less time than men, and certain periods of day are dedicated to specific activities. Extension activities must match the time and place specified by women. The extension needs of men and women differ. Women need direct extension on the crops and livestock they grow or have responsibility for. A priority of extension services should be facilitating women's access to labor-saving technology. Male extension workers should be taught how to approach women producers in a culturally acceptable manner.